Demiclosed Principle for Asymptotically Nonexpansive Mappings in CAT(0) Spaces - Nanjaras,B. (Springer Publishing Company, 2015)
We prove the demiclosed principle for asymptotically nonexpansive mappings in CAT(0) spaces. As a consequence, we obtain a Δ-convergence theorem of the Krasnosel'skii-Mann iteration for asymptotically nonexpansive mappings in this setting. Our results extend and improve many results in the literature. Copyright © 2010 B. Nanjaras and B. Panyanak.